Question and Answers Forum

All Questions      Topic List

Mechanics Questions

Previous in All Question      Next in All Question      

Previous in Mechanics      Next in Mechanics      

Question Number 214449 by ajfour last updated on 08/Dec/24

Commented by ajfour last updated on 09/Dec/24

https://youtu.be/mVW8FiNpKjk?si=q68kdETxCuqwyZ3-

Answered by mr W last updated on 14/Dec/24

Commented by mr W last updated on 15/Dec/24

(X, Y) =center of lower cylinder  (x, y) =center of upper cylinder  X=−r sin θ  Y=r  x=r sin θ  y=r+2r cos θ  let ω=(dθ/dt)  V_x =−(dX/dt)=ωr cos θ  V_y =0  v_x =(dx/dt)=ωr cos θ  v_y =−(dy/dt)=2ωr sin θ  both cylinders obtain no rotation.  2mgr(1−cos θ)=((mω^2 r^2 cos^2  θ)/2)+((mω^2 r^2 (cos^2  θ+4 sin^2  θ))/2)  2g(1−cos θ)=ω^2 r(1+sin^2  θ)  ⇒ω^2 =((2g(1−cos θ))/(r(1+sin^2  θ)))  2ω(dω/dθ)=((2g)/r)[((sin θ)/(1+sin^2  θ))−((2(1−cos θ) sin θ cos θ)/((1+sin^2  θ)^2 ))]  ω(dω/dθ)=((g sin θ (cos^2  θ−2 cos θ+2))/(r(1+sin^2  θ)^2 ))  A_x =(dV_x /dt)=ω(dV_x /dθ)=ωr(−ω sin θ+cos θ (dω/dθ))  A_x =g[−((2 sin θ(1−cos θ))/((1+sin^2  θ)))+((sin θ cos θ(cos^2  θ−2 cos θ+2))/((1+sin^2  θ)^2 ))]  A_x =((g sin θ(−cos^3  θ+6 cos θ−4))/((1+sin^2  θ)^2 ))  N sin θ=mA_x   ⇒(N/(mg))=((−cos^3  θ+6 cos θ−4)/((1+sin^2  θ)^2 ))  when N=0,  cos^3  θ−6 cos θ+4=0  (cos θ−2)(cos^2  θ+2 cos θ−2)=0  0<cos θ<1 ⇒only one root is suitable  cos θ=(√3)−1  ⇒θ=cos^(−1) ((√3)−1)≈42.941°  ==================  V_x =ωr cos θ=cos θ(√((2gr(1−cos θ))/(1+sin^2  θ)))  V_(x,final) =(√((3(√3)−5)gr))≈0.4429(√(gr))  this is the final speed of the lower  cylinder after separation from the  upper cylinder.

$$\left({X},\:{Y}\right)\:={center}\:{of}\:{lower}\:{cylinder} \\ $$$$\left({x},\:{y}\right)\:={center}\:{of}\:{upper}\:{cylinder} \\ $$$${X}=−{r}\:\mathrm{sin}\:\theta \\ $$$${Y}={r} \\ $$$${x}={r}\:\mathrm{sin}\:\theta \\ $$$${y}={r}+\mathrm{2}{r}\:\mathrm{cos}\:\theta \\ $$$${let}\:\omega=\frac{{d}\theta}{{dt}} \\ $$$${V}_{{x}} =−\frac{{dX}}{{dt}}=\omega{r}\:\mathrm{cos}\:\theta \\ $$$${V}_{{y}} =\mathrm{0} \\ $$$${v}_{{x}} =\frac{{dx}}{{dt}}=\omega{r}\:\mathrm{cos}\:\theta \\ $$$${v}_{{y}} =−\frac{{dy}}{{dt}}=\mathrm{2}\omega{r}\:\mathrm{sin}\:\theta \\ $$$${both}\:{cylinders}\:{obtain}\:{no}\:{rotation}. \\ $$$$\mathrm{2}{mgr}\left(\mathrm{1}−\mathrm{cos}\:\theta\right)=\frac{{m}\omega^{\mathrm{2}} {r}^{\mathrm{2}} \mathrm{cos}^{\mathrm{2}} \:\theta}{\mathrm{2}}+\frac{{m}\omega^{\mathrm{2}} {r}^{\mathrm{2}} \left(\mathrm{cos}^{\mathrm{2}} \:\theta+\mathrm{4}\:\mathrm{sin}^{\mathrm{2}} \:\theta\right)}{\mathrm{2}} \\ $$$$\mathrm{2}{g}\left(\mathrm{1}−\mathrm{cos}\:\theta\right)=\omega^{\mathrm{2}} {r}\left(\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta\right) \\ $$$$\Rightarrow\omega^{\mathrm{2}} =\frac{\mathrm{2}{g}\left(\mathrm{1}−\mathrm{cos}\:\theta\right)}{{r}\left(\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta\right)} \\ $$$$\mathrm{2}\omega\frac{{d}\omega}{{d}\theta}=\frac{\mathrm{2}{g}}{{r}}\left[\frac{\mathrm{sin}\:\theta}{\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta}−\frac{\mathrm{2}\left(\mathrm{1}−\mathrm{cos}\:\theta\right)\:\mathrm{sin}\:\theta\:\mathrm{cos}\:\theta}{\left(\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta\right)^{\mathrm{2}} }\right] \\ $$$$\omega\frac{{d}\omega}{{d}\theta}=\frac{{g}\:\mathrm{sin}\:\theta\:\left(\mathrm{cos}^{\mathrm{2}} \:\theta−\mathrm{2}\:\mathrm{cos}\:\theta+\mathrm{2}\right)}{{r}\left(\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta\right)^{\mathrm{2}} } \\ $$$${A}_{{x}} =\frac{{dV}_{{x}} }{{dt}}=\omega\frac{{dV}_{{x}} }{{d}\theta}=\omega{r}\left(−\omega\:\mathrm{sin}\:\theta+\mathrm{cos}\:\theta\:\frac{{d}\omega}{{d}\theta}\right) \\ $$$${A}_{{x}} ={g}\left[−\frac{\mathrm{2}\:\mathrm{sin}\:\theta\left(\mathrm{1}−\mathrm{cos}\:\theta\right)}{\left(\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta\right)}+\frac{\mathrm{sin}\:\theta\:\mathrm{cos}\:\theta\left(\mathrm{cos}^{\mathrm{2}} \:\theta−\mathrm{2}\:\mathrm{cos}\:\theta+\mathrm{2}\right)}{\left(\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta\right)^{\mathrm{2}} }\right] \\ $$$${A}_{{x}} =\frac{{g}\:\mathrm{sin}\:\theta\left(−\mathrm{cos}^{\mathrm{3}} \:\theta+\mathrm{6}\:\mathrm{cos}\:\theta−\mathrm{4}\right)}{\left(\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta\right)^{\mathrm{2}} } \\ $$$${N}\:\mathrm{sin}\:\theta={mA}_{{x}} \\ $$$$\Rightarrow\frac{{N}}{{mg}}=\frac{−\mathrm{cos}^{\mathrm{3}} \:\theta+\mathrm{6}\:\mathrm{cos}\:\theta−\mathrm{4}}{\left(\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta\right)^{\mathrm{2}} } \\ $$$${when}\:{N}=\mathrm{0}, \\ $$$$\mathrm{cos}^{\mathrm{3}} \:\theta−\mathrm{6}\:\mathrm{cos}\:\theta+\mathrm{4}=\mathrm{0} \\ $$$$\left(\mathrm{cos}\:\theta−\mathrm{2}\right)\left(\mathrm{cos}^{\mathrm{2}} \:\theta+\mathrm{2}\:\mathrm{cos}\:\theta−\mathrm{2}\right)=\mathrm{0} \\ $$$$\mathrm{0}<\mathrm{cos}\:\theta<\mathrm{1}\:\Rightarrow{only}\:{one}\:{root}\:{is}\:{suitable} \\ $$$$\mathrm{cos}\:\theta=\sqrt{\mathrm{3}}−\mathrm{1} \\ $$$$\Rightarrow\theta=\mathrm{cos}^{−\mathrm{1}} \left(\sqrt{\mathrm{3}}−\mathrm{1}\right)\approx\mathrm{42}.\mathrm{941}° \\ $$$$================== \\ $$$${V}_{{x}} =\omega{r}\:\mathrm{cos}\:\theta=\mathrm{cos}\:\theta\sqrt{\frac{\mathrm{2}{gr}\left(\mathrm{1}−\mathrm{cos}\:\theta\right)}{\mathrm{1}+\mathrm{sin}^{\mathrm{2}} \:\theta}} \\ $$$${V}_{{x},{final}} =\sqrt{\left(\mathrm{3}\sqrt{\mathrm{3}}−\mathrm{5}\right){gr}}\approx\mathrm{0}.\mathrm{4429}\sqrt{{gr}} \\ $$$${this}\:{is}\:{the}\:{final}\:{speed}\:{of}\:{the}\:{lower} \\ $$$${cylinder}\:{after}\:{separation}\:{from}\:{the} \\ $$$${upper}\:{cylinder}. \\ $$

Commented by ajfour last updated on 15/Dec/24

Really glad for the same conclusion, sir.

Answered by ajfour last updated on 09/Dec/24

Commented by ajfour last updated on 04/Jan/25

mg(2r)(1−cos θ)=mV^2 +(1/2)mv^2   Vsin θ=vcos θ−Vsin θ   &  mgcos θ−(N=0)−(mAsin θ=0)         =m(((2Vcos θ+vsin θ)^2 )/(2r))  ⇒  2Vcos θ +vsin θ=(√(2grcos θ))         2Vsin θ=vcos θ  ⇒  v(((cos^2 θ)/(sin θ))+sin θ)=(√(2grcos θ))  v^2 =2grcos θsin^2 θ  V^(  2 ) =((grcos^3 θ)/2)    hence  2(1−cos θ)=((cos^3 θ)/2)+cos θ(1−cos^2 θ)  If cos θ=c  ⇒ 2−2c=−(c^3 /2)+c  c^3 −6c+4=0  has just one root c=(√3)−1  θ=cos^(−1) ((√3)−1)   V^2 =((grcos^3 θ)/2)  V=(√(gr(3(√3)−5)))

$${mg}\left(\mathrm{2}{r}\right)\left(\mathrm{1}−\mathrm{cos}\:\theta\right)={mV}^{\mathrm{2}} +\frac{\mathrm{1}}{\mathrm{2}}{mv}^{\mathrm{2}} \\ $$$${V}\mathrm{sin}\:\theta={v}\mathrm{cos}\:\theta−{V}\mathrm{sin}\:\theta\:\:\:\& \\ $$$${mg}\mathrm{cos}\:\theta−\left({N}=\mathrm{0}\right)−\left({mA}\mathrm{sin}\:\theta=\mathrm{0}\right) \\ $$$$\:\:\:\:\:\:\:={m}\frac{\left(\mathrm{2}{V}\mathrm{cos}\:\theta+{v}\mathrm{sin}\:\theta\right)^{\mathrm{2}} }{\mathrm{2}{r}} \\ $$$$\Rightarrow\:\:\mathrm{2}{V}\mathrm{cos}\:\theta\:+{v}\mathrm{sin}\:\theta=\sqrt{\mathrm{2}{gr}\mathrm{cos}\:\theta} \\ $$$$\:\:\:\:\:\:\:\mathrm{2}{V}\mathrm{sin}\:\theta={v}\mathrm{cos}\:\theta \\ $$$$\Rightarrow\:\:{v}\left(\frac{\mathrm{cos}\:^{\mathrm{2}} \theta}{\mathrm{sin}\:\theta}+\mathrm{sin}\:\theta\right)=\sqrt{\mathrm{2}{gr}\mathrm{cos}\:\theta} \\ $$$${v}^{\mathrm{2}} =\mathrm{2}{gr}\mathrm{cos}\:\theta\mathrm{sin}\:^{\mathrm{2}} \theta \\ $$$${V}^{\:\:\mathrm{2}\:} =\frac{{gr}\mathrm{cos}\:^{\mathrm{3}} \theta}{\mathrm{2}}\:\:\:\:{hence} \\ $$$$\mathrm{2}\left(\mathrm{1}−\mathrm{cos}\:\theta\right)=\frac{\mathrm{cos}\:^{\mathrm{3}} \theta}{\mathrm{2}}+\mathrm{cos}\:\theta\left(\mathrm{1}−\mathrm{cos}\:^{\mathrm{2}} \theta\right) \\ $$$${If}\:\mathrm{cos}\:\theta={c} \\ $$$$\Rightarrow\:\mathrm{2}−\mathrm{2}{c}=−\frac{{c}^{\mathrm{3}} }{\mathrm{2}}+{c} \\ $$$${c}^{\mathrm{3}} −\mathrm{6}{c}+\mathrm{4}=\mathrm{0} \\ $$$${has}\:{just}\:{one}\:{root}\:{c}=\sqrt{\mathrm{3}}−\mathrm{1} \\ $$$$\theta=\mathrm{cos}^{−\mathrm{1}} \left(\sqrt{\mathrm{3}}−\mathrm{1}\right)\: \\ $$$${V}^{\mathrm{2}} =\frac{{gr}\mathrm{cos}\:^{\mathrm{3}} \theta}{\mathrm{2}} \\ $$$${V}=\sqrt{{gr}\left(\mathrm{3}\sqrt{\mathrm{3}}−\mathrm{5}\right)} \\ $$$$ \\ $$

Commented by ajfour last updated on 09/Dec/24

https://youtu.be/pHHTfPtRV98?si=JtR34MdARBkxuPIV

Terms of Service

Privacy Policy

Contact: info@tinkutara.com